2018
DOI: 10.3390/ijerph15040630
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Waste in Popular Beaches in Thailand: High Densities that Demand Environmental Action

Abstract: Thailand, like all nations, has a responsibility to initiate environmental actions to preserve marine environments. Low- and middle-income countries face difficulties implementing feasible strategies to fulfill this ambitious goal. To contribute to the revitalization of Thailand’s marine ecosystems, we investigated the level of tobacco product waste (TPW) on Thailand’s public beaches. We conducted a cross-sectional observational survey at two popular public beaches. Research staff collected cigarette butts ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 25 publications
1
6
0
2
Order By: Relevance
“…Principal beach litter composition expressed as number of total items per group(s), are presented in Table 1. Much of these items are discarded by beach users, in particular cigarette butts, which was the most abundant item in this paper's research, as has also been observed at other bathing areas by Martinez-Ribes et al ( 2007), Oigman-Pszczol & Creed ( 2007), Topçu et al (2013), Williams et al (2016b) and Kungskulniti et al (2018). Specifically, the number of cigarette butts recorded in spring (4,607 units) tripled in summer (12,843 units).…”
Section: Litter Magnitudes and Compositionsupporting
confidence: 73%
See 1 more Smart Citation
“…Principal beach litter composition expressed as number of total items per group(s), are presented in Table 1. Much of these items are discarded by beach users, in particular cigarette butts, which was the most abundant item in this paper's research, as has also been observed at other bathing areas by Martinez-Ribes et al ( 2007), Oigman-Pszczol & Creed ( 2007), Topçu et al (2013), Williams et al (2016b) and Kungskulniti et al (2018). Specifically, the number of cigarette butts recorded in spring (4,607 units) tripled in summer (12,843 units).…”
Section: Litter Magnitudes and Compositionsupporting
confidence: 73%
“…cigarette butts. Despite their small dimensions, they can cause multiple harmful impacts, as evidenced by Kungskulniti et al (2018). Some studies present data on litter weight, but this can lead to confusion due to the difference in size and type of material for each item.…”
Section: Beach Typology and Litter Gradementioning
confidence: 99%
“…Other studies registered a high volume of discarded cigarette butts in these environments. (17) While we found some examples of smoke-free beaches in Spain, (42) this is not universal. Still, the results found in previous studies suggest that beaches may be an important site for policy intervention.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, these studies focused their results on the identification of types of places that may constitute hotspots for cigarette butt litter in outdoor environments (i.e. beaches, (17) parks, (18) public transportation stops (14) or hospitality venues, (19)). However, this earlier work limited their results to these places and overlooked the extent of the exposure in the across wider geographical areas, such as a city.…”
Section: Introductionmentioning
confidence: 99%
“…Within beach litter, cigarette butts (CB) constitute one of the most abundant items. The presence of this type of personal waste has been very well documented in different beaches around the world [8][9][10][11][12][13], including Spain [14][15][16]. Their presence on the coast can be used as an indicator of beach management efficiency [17], environmental consciousness [18] and beach pollution linked to beachgoers [19].…”
Section: Introductionmentioning
confidence: 99%